STRATIGRAPHY AND SEDIMENTOLOGY OF A DRY TO WET EOLIAN DEPOSITIONAL SYSTEM, BURNS FORMATION, MERIDIANI PLANUM, MARS - Grotzinger J.P.; Fike D.A.; Watters W.A.; Arvidson R.E.; Jolliff B.L.; Sohl-Dickstein J.N.; Squyres S.W.; Bell III J.F.; Calvin W.; Clark B.C.; Parker T.; Golombek M.; et al. (My University, 2005)
Outcrop exposures of sedimentary rocks at the Opportunity landing site (Meridiani Planum) form a set of genetically related strata defined here informally as the Burns formation. This formation can be subdivided into lower, middle, and upper units which, respectively, represent eolian dune, eolian sand sheet, and mixed eolian sand sheet and interdune facies associations. Collectively, these three units are at least 7 m thick and define a “wetting-upward” succession which records a progressive increase in the influence of groundwater and, ultimately, surface water in controlling primary depositional processes.